Recreation planning and design. - Gold, Seymour M. (New York McGraw-Hill Book Company, 1980)
Light rubbing wear to cover, spine and page edges. Very minimal writing or notations in margins not affecting the text. Possible clean ex-library copy, with their stickers and or stamp(s).
Keywords: Culture